Marketing performance and factors influencing farmers choice for agricultural output marketing channels: the case of garden pea (Pisum sativum) in India - Thakur, Pankaj; Mehta, Piyush; Devi, Chhaya; Sharma, Prashant; Singh, Krishna Kumar; Yadav, Shikha; Lal, Priyanka; Raghav, Yashpal Singh; Kapoor, Promil; Mishra, Pradeep (Frontiers in Sustainable Food Systems, 2023)
Agriculture is the backbone of Indian economy and farmers play significant role in sustaining the sector. However, farmers face several challenges such as poor market access and limited access to market information which adversely affect their marketing performance. Therefore, this study aimed to examine the marketing performance and factors influencing farmers choice for agricultural output marketing channels in garden pea in the Indian state of Himachal Pradesh. The study utilized primary data collected through structured questionnaires administered via the interview method to a sample size of 400 farmers selected through a multistage stratified random sampling technique. The data collected were analyzed using descriptive statistics and acharya approach to study the marketing performance. Further, a multinomial logistic regression model was used to determine the factors that influence farmers marketing choice of marketing channels. Additionally, the constraints experienced by farmers during marketing were investigated using garret ranking. The study revealed that farmers who sold their pea directly to consumer had higher marketing performance than those who sold through market intermediaries such as local traders, commission agents and wholesalers. Further, the results indicated that farm income, farm experience, distance to the market and market information were significant determinants of farmers choice for marketing channels. Whereas, lack of market consultancy, high commission chargers and poor transportation were the major constraints faced by farmers during marketing of pea. The findings of this study highlight the need for policymakers to develop and implement interventions that enhance farmers marketing skill, facilitate access to markets, improve negotiation power which can lead to higher incomes for farmers, improve their livelihoods, better quality produce for consumers and a more efficient and sustainable food system.